White-matter hyperintensities in first-episode psychosis - Zanetti, Marcus V. (Royal College Of Psychiatrists, 2008)
Background White-matter hyperintensities have been associated with both schizophrenia and mood disorders, particularly bipolar disorder, but results are inconsistent across studies. Aims To examine whether white-matter hyperintensities are a vulnerability marker for psychosis or are specifically associated with bipolar disorder. Method T(2)-weighted magnetic resonance imaging data were acquired in 129 individuals with first-episode psychosis (either affective or non-affective psychoses) and 102 controls who were randomly selected from the same geographical areas. Visual white-matter hyperintensity ratings were used for group and subgroup comparisons. Results There were no statistically significant between-group differences in white-matter hyperintensity frequency or severity scores. No significant correlations were found between white-matter hyperintensity scores and duration of illness, duration of untreated psychosis, or severity of psychotic, manic or depressive symptoms. Conclusions White-matter hyperintensities are not associated with vulnerability to psychosis in general, or specifically with affective psychoses. Further, first-episode psychosis investigations using more quantitative methods are warranted to confirm these findings.